2017
DOI: 10.1016/j.cmi.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Management of post-neurosurgical meningitis: narrative review

Abstract: Guiding the optimal management of PNM will necessitate collaborative multicentre efforts and unique study designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 82 publications
2
81
0
1
Order By: Relevance
“…EVDs and ICPs were inserted in the operating room, while most LDs were inserted on the ward at bedside. Meningitis was managed according to published and local guidelines, the latter considering the local epidemiology [13,35].…”
Section: Methodsmentioning
confidence: 99%
“…EVDs and ICPs were inserted in the operating room, while most LDs were inserted on the ward at bedside. Meningitis was managed according to published and local guidelines, the latter considering the local epidemiology [13,35].…”
Section: Methodsmentioning
confidence: 99%
“…Generally, as is common in other surgical practice, the risk factor of inserting device infection, the venue of procedure and the surgical technique are know by surgeon's experience. 27 Wound culture were dominated with GPB (71.87%), with isolate was S. aureus (39.13%) and followed GNB P. aeruginosa (55.56%). Negi et.al are found 96,4% surgical site infection yielding bacteria growth with S. aureus (54.4%), P. aeruginosa (21.7%) and E. coli.…”
mentioning
confidence: 95%
“…Routine CSF analysis, such as glucose levels, cell counts and protein concentration are retained by most authors as criteria to diagnose PBM 1012 . In many diagnostic studies in patients with PBM, CSF routine examinations, including WBC and neutrophil counts, protein levels and hypoglycorrhachia, were neither specific nor associated with high positive and negative predictive values 13 . Tamune et al demonstrated that the CSF/blood glucose ratio may predict the presence of bacterial meningitis more precisely than other routinely measured markers in CSF 14 .…”
Section: Discussionmentioning
confidence: 93%